Flipped Learning in TEYL Class: The Implementation and Students Perception - Vonti, Lungguh Halira; Andovita, Leora Grahadila (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2021)
The study is aimed to describe the implementation of flipped learning and also to know the students perception toward the implementation of flipped learning in TEYL class. The study was conducted to the seventh semester students of English Education Study Program in Faculty of Teachers Training and Educational Sciences, Pakuan University. The method of the study is descriptive experimental research. The result of the study showed that the lecturer's overall experience in the course was quite encouraging and motivating for other lecturers or researchers as that the student engagement to the material was improved, and there were many active discussions of the material took place in the classroom activities, and the students also expanded their learning skills as they needed to read and review the material independently. Based on the students' point of view, related to their perception of the implementation of flipped learning, most of them gave positive perception since they stated that the learning model was motivating and also gave them opportunities to interact with their friends and lecturer.